2010
DOI: 10.1186/1471-2407-10-517
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulation of CD44in Hodgkin and non-Hodgkin lymphoma

Abstract: BackgroundEpigenetic inactivation of tumor suppressor genes (TSG) by promoter CpG island hypermethylation is a hallmark of cancer. To assay its extent in human lymphoma, methylation of 24 TSG was analyzed in lymphoma-derived cell lines as well as in patient samples.MethodsWe screened for TSG methylation using methylation-specific multiplex ligation-dependent probe amplification (MS-MLPA) in 40 lymphoma-derived cell lines representing anaplastic large cell lymphoma, Burkitt lymphoma (BL), diffuse large B-cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 51 publications
(50 reference statements)
3
19
0
Order By: Relevance
“…The interactions of these receptors with hyaluronan within ECM facilitate cell motility and adhesion. Promoter methylation is known to regulate CD44 expression, where hypermethylation results in transcriptional inactivation 40 ; however, epigenetic regulation of HMMR is largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The interactions of these receptors with hyaluronan within ECM facilitate cell motility and adhesion. Promoter methylation is known to regulate CD44 expression, where hypermethylation results in transcriptional inactivation 40 ; however, epigenetic regulation of HMMR is largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…It is identified as a senescence-induced cell adhesion gene responsible for monocyte recruitment (Mun and Boo, 2010). In lymphoma and lymphoma cell lines, it is an epigenetically suppressed inducer of apoptosis (Eberth et al, 2010). On the other hand, CD44 expression enhances growth, self renewal and tumorosphere formation in breast carcinoma cell lines .…”
Section: Csc-tpc Biomarkersmentioning
confidence: 99%
“…Other examples abound. In a panel of human breast cancer cell lines, there is a parallelism between an EMT mRNA or other marker signatures and the CSC-TPC (CD44 þ /CD24 þ /À ) phenotype (Mani et al, 2008;Blick et al, 2010;Eberth et al, 2010). The two programs EMT and CSC-TPC are induced by activation of Ras (Morel et al, 2008) and TGF-b actors.…”
Section: Common Properties Of Emt Cells and Classical Cscsmentioning
confidence: 99%
“…This is often associated with gene silencing [Jones and Laird, 1999] and is an important mechanism for the inactivation of tumor suppressor genes. In more recent studies on DNA methylation and cancers, Eberth et al [2010] found that CD44 may be a promising new epigenetic marker for diagnosis and a potential therapeutic target for the treatment of specific lymphoma subtypes as it is found to be epigenetically regulated in lymphoma and undergoes de novo methylation in distinct lymphoma subtypes; Bediaga et al [2010] found that DNA methylation profiles may enable breast cancer subtype prediction; Christensen et al [2010] found that breast cancer prognostic characteristics and risk-related exposures appear to be associated with gene-specific tumor methylation and overall methylation pattern; and Lugthart et al [2011] found aberrant DNA hypermethylation in acute myeloid leukemia among many other studies. Apart from the importance in DNA methylation with cancer development, what makes DNA methylation even more interesting is, unlike genetic alterations, DNA methylation is reversible.…”
Section: Introductionmentioning
confidence: 99%